Acta Neurochirurgica Supplements
DOI: 10.1007/978-3-211-33081-4_40
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar and thalamic stimulation treatment for epilepsy

Abstract: The present chapter describes the most important available experimental and clinical evidence on the role of electrical stimulation of the cerebellum or the thalamus in the control of epilepsy. Cerebellum serves as an integrator of sensory information and regulator of motor coordinating and training. The sole output of the cerebellum is inhibitory Purkinje cell projections to deep cerebellar nuclei in the brainstem. Cerebellar stimulation in animal models of epilepsy has given mixed results. Nevertheless, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
5

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 61 publications
1
69
0
5
Order By: Relevance
“…34 The previously proposed theory that stimulation of the Purkinje cells may intensify the inhibitory cerebellar output to the thalamic neuronal network, and subsequently weaken its excitatory output to the cerebral cortex, cannot be supported by the histopathological findings of several animal and human reports. These reports described significantly decreased populations of Purkinje cells in epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 The previously proposed theory that stimulation of the Purkinje cells may intensify the inhibitory cerebellar output to the thalamic neuronal network, and subsequently weaken its excitatory output to the cerebral cortex, cannot be supported by the histopathological findings of several animal and human reports. These reports described significantly decreased populations of Purkinje cells in epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…9,18,54 It has been proven that stimulation of the cerebellar cortex resulted in further degeneration and population decrease of Purkinje cells. 34 In addition, Dow et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pooled analysis of prior small series has recently been published by Krauss and Koubeissi [56], demonstrating a seizure freedom rate of 27 % (31/115 patients) and at minimum a reduction of seizures in 76 % (87/115 patients) in the prior, heterogeneous case series. More rigorously controlled studies across 17 patients found none seizure free and 5/17 with reduced seizures.…”
Section: Cerebellummentioning
confidence: 99%
“…Only 2 patients out of 17 benefited from this procedure [37]. However, a recent study reported that stimulation of the superior-mesial cerebellar cortex in 5 patients with generalised tonicoclonic seizures (4 patients also with tonic seizures), led to a reduction but not complete suppression of tonicoclonic or clonic seizures after 24 months [38].…”
Section: Deep Brain Stimulationmentioning
confidence: 99%